Occupational therapy graduates' perceptions and experiences of intrapreneurship in contrasting healthcare practice contexts - Roe, Sarah A. (2019)
Recent UK Government rhetoric is calling for healthcare professionals to practice entrepreneurially whilst they are simultaneously being bombarded with restrictive protocols and prescriptive regimens. There is little agreement concerning what entrepreneurship is and the term ‘intrapreneurship’ has recently entered the literature field denoting the innovative and creative practices within an organisation. There is little usable inquiry into this important field, with the healthcare practice context severely lagging behind the wider entrepreneurship debates. This has created a highly pressured and confusing landscape for new occupational therapy graduates to negotiate.